CLASSIFICATION OF ENGLISH AND UZBEK PROVERBS CONTAINING THE NAMES OF MEDICAL PERSONNEL ACCORDING TO DIFFERENT CHARACTERISTICS - Chorieva, Iroda (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article delves into the fascinating realm of proverbs that incorporate the names of medical personnel, such as doctors, nurses, and pharmacists. Drawing upon a diverse range of cultural and linguistic sources, this study explores the origins, meanings, and cultural significance of these unique proverbs. By examining the ways in which medical personnel are metaphorically represented in proverbial wisdom, this article sheds light on the intersection of medicine, language, and culture.